2018
DOI: 10.20944/preprints201811.0375.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the Awareness, Attitude and Environmental Literacy about Environmental Issues and Challenges (Case Study: Yazd Citizen’s View in 2017)

Abstract: Introduction: Different factors such as rapid growth of population, urbanization and industrialization of communities have detrimental effects on the environment. In regard to the importance of the environment and its fundamental role in sustainable development along with the awareness and attitude of the people of Yazd which has not yet been assessed, this study aims to assess the level of awareness, attitude and environmental literacy of the people of Yazd in relation to environmental issues and challenges i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…S. (2015) had showed that the attention ranges in the direction of pollutants of human beings in Kanyakumari District are tremendous and the pollutants likes water, air, plastic, soil and so on conscious via way of means of them. Mihanpour H. et al (2018), their gift look at, there has been no big courting among gender, schooling degree, marital repute, region of residence, consciousness degree and mindset ranges in addition to The consciousness rating became statistically big when it comes to the age, schooling degree and employment repute variables. Yunus, et al (2019), their look at found out that the effectiveness of those factors consisting of mindset, behaviour, demographics and perception.…”
Section: Literature Reviewmentioning
confidence: 99%
“…S. (2015) had showed that the attention ranges in the direction of pollutants of human beings in Kanyakumari District are tremendous and the pollutants likes water, air, plastic, soil and so on conscious via way of means of them. Mihanpour H. et al (2018), their gift look at, there has been no big courting among gender, schooling degree, marital repute, region of residence, consciousness degree and mindset ranges in addition to The consciousness rating became statistically big when it comes to the age, schooling degree and employment repute variables. Yunus, et al (2019), their look at found out that the effectiveness of those factors consisting of mindset, behaviour, demographics and perception.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental literacy in students is currently still in the stage of growing awareness and concern while responsibility has not become a real behavior / participation and has not been based on strong knowledge. Environmental literacy is a person's level of awareness of the environment which includes 7 components (Mihanpour et al, 2018;Nasution, 2021). However, for the junior high school level, the appropriate components in assessing students' environmental literacy are 4 components, namely ecological knowledge, cognitive skills, attitudes and behavior.…”
Section: Article Historymentioning
confidence: 99%